ANALISIS FAKTOR TINGKAT PENDIDIKAN DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. TRAKTOR NUSANTARA CABANG LAMPUNG - Raditee Sanusi Husin (Universitas Sang Bumi Ruwa Jurai, 2017)
Achievement of company goals, PT. Traktor Nusantara often faces problems, where from within and from outside the company. One of the problems that comes from within the company in relation to human resources is the level of work productivity of employees who are still far from expectation. This is allegedly caused by the level of employee education that has not been in accordance with the function of office, in addition to the competence of employees who have not been in accordance with the field of work. This study aims to determine the influence of education level and competence on employee productivity. The sample used is 22 employees. Data collection techniques with questionnaires, documentation and observation. Data analysis with qualitative and quantitative analysis methods with the help of statistical tools SPSS application for linear regression model calculation. The results showed that the level of education has a positive influence on the productivity of employees of PT. Traktor Nusantara. The amount of influence of education level variable to productivity based on test of determination is equal to 38,1%. Competence influence on work productivity of employees of PT. Traktor Nusantara with contribution of 19.1%. The level of education and competence together have a positive influence and able to explain 38.2% of the changes in work productivity, while the remaining 4.7% sebesat is another variable outside the study.